Same-Sex Mothers and Lactation. Issue 3 (May 2019) - Juntereal, Nina A.; Spatz, Diane L.
Abstract : Abstract: Investigation of the needs of same-sex mothers practicing lactation is limited in the nursing literature. The heteronormative structure of the healthcare system has stigmatized these postpartum women and minimized the level of nursing care provided. Case reports demonstrate that same-sex mothers value inclusivity and understanding of their healthcare needs that is missing in healthcare settings. Perinatal nurses must listen attentively and think critically about their words and actions to avoid inappropriate judgments when providing care to this population. Active engagement and ongoing competence education builds the foundation that will provide perinatal nurses the knowledge they need to best support the unique needs of same-sex mothers in their lactation experience. Abstract : There are very limited data about same-sex mothers and lactation. In this study, women who are part of a same-sex couple and had recently given birth were interviewed about their breastfeeding experiences. The findings are helpful to nurses who care for this population and can be the basis for appropriate and sensitive care.